Ambulatory heart rate reduction after catheter-based renal denervation in hypertensive patients not receiving anti-hypertensive medications: data from SPYRAL HTN-OFF MED, a randomized, sham-controlled, proof-of-concept trial. (4th January 2019) - Böhm, Michael; Mahfoud, Felix; Townsend, Raymond R; Kandzari, David E; Pocock, Stuart; Ukena, Christian; Weber, Michael A; Hoshide, Satoshi; Patel, Manesh; Tyson, Crystal C; Weil, Joachim; Agdirlioglu, Tolga; et al.
Abstract: Aims: The randomized sham-controlled SPYRAL HTN-OFF MED trial demonstrated that renal denervation (RDN) using a multi-electrode catheter lowers ambulatory blood pressure (BP) in non-medicated hypertensive patients. The current report describes the effects of RDN on heart rate (HR) in this population. Methods and results: Patients were enrolled with an office systolic BP (SBP) of ≥150 mmHg and <180 mmHg, office diastolic BP (DBP) of ≥90 mmHg, and a mean ambulatory SBP of ≥140 mmHg and <170 mmHg. Patients were drug naïve or removed from their anti-hypertensive medications. Eighty patients were randomized 1:1 to RDN or sham procedure. This post hoc analysis examines the effect at 3 months of RDN on HR and of high baseline 24-h HR on BP and HR changes. There was a significant reduction in 24-h HR at 3 months for the RDN group (−2.5 b.p.m.) compared with sham (−0.2 b.p.m.), P = 0.003 (analysis of covariance). Mean baseline-adjusted treatment differences were significantly different between groups at 3 months for average morning HR (−4.4 b.p.m., P = 0.046) and minimum morning HR (−3.0 b.p.m., P = 0.026). RDN patients with baseline 24-h HR above the median (73.5 b.p.m.) had significant reductions in average ambulatory SBP (−10.7 mmHg difference, P = 0.001) and DBP (−7.5 mmHg, P < 0.001), whereas BP changes in RDN patients with below-median HRs were not significant. Conclusion: Average and minimum morning HR were significantly reduced at 3 months for RDN compared with sham patients. A baseline 24-h HR above the median predicted greater BP reductions and may allow physicians to select patients likely to respond to the procedure.